2017
DOI: 10.1111/eip.12453
|View full text |Cite
|
Sign up to set email alerts
|

What impact does trauma have on the at‐risk mental state? A systematic literature review

Abstract: Identification of individuals with an at-risk mental state (ARMS) who are at a heightened risk of developing psychosis allows researchers and clinicians to identify what factors are associated with poorer outcomes and transitions to psychosis. A number of socioenvironmental factors are linked to an increase risk of developing psychosis, of which childhood trauma is widely acknowledged. The current review aims to examine what impact trauma has on the ARMS by reviewing reported relationships between trauma varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
(83 reference statements)
0
13
0
2
Order By: Relevance
“…Most systematic reviews were conducted on individuals with psychotic disorders (Read et al ., 2003; Morgan and Fisher, 2007; Bonoldi et al ., 2013; de Sousa et al ., 2014), or specifically in people with schizophrenia (Matheson et al ., 2013). Some reviews broadened the scope to include both psychotic disorders and any psychotic experiences (Varese et al ., 2012), while others included studies that report only the severity of psychotic experiences in the general population (van Dam et al ., 2012; Trotta et al ., 2015) or the UHR population (Fusar-Poli et al ., 2013, 2016; Kraan et al ., 2015 b ; Brew et al ., 2017).…”
mentioning
confidence: 99%
“…Most systematic reviews were conducted on individuals with psychotic disorders (Read et al ., 2003; Morgan and Fisher, 2007; Bonoldi et al ., 2013; de Sousa et al ., 2014), or specifically in people with schizophrenia (Matheson et al ., 2013). Some reviews broadened the scope to include both psychotic disorders and any psychotic experiences (Varese et al ., 2012), while others included studies that report only the severity of psychotic experiences in the general population (van Dam et al ., 2012; Trotta et al ., 2015) or the UHR population (Fusar-Poli et al ., 2013, 2016; Kraan et al ., 2015 b ; Brew et al ., 2017).…”
mentioning
confidence: 99%
“…Patients with a variety of mental disorders often report CEs [32][33][34][35][36][37][38][39][40][41][42][43]. In our previous study [17], patients with mood disorders reported CEs more often than non-psychiatric individuals investigated in an earlier study [61].…”
Section: Tablementioning
confidence: 96%
“…The investigation was undertaken with a relatively large and representative sample of mood disorder patients recruited from specialized psychiatric care, and extensive data of self-reported symptoms and experiences was collected. Moreover, we examined a comprehensive set of self-reported data of CEs, an important factor in the aetiology of mood disorders, psychosis and BPD [32][33][34][35][36][37][38][39][40].…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Różne badania wskazują na związek doświadczeń urazowych z nasileniem objawów pozytywnych, afektywnych i poznawczych, a także z zaburzeniami percepcji (Loewy et al, 2019;O'Connor et al, 2019), choć nie we wszystkich badaniach zależności te są spójnie wykazywane (de Vos et al, 2019). Zwraca się uwagę, że wpływ traumy na nasilenie objawów i poziom funkcjonowania pacjenta zależy od kilku czynników: dawki (czyli ilości), jakości i przewlekłości doświadczeń urazowych (Brew et al, 2018). Doświadczenia te mogą się przyczyniać do rozwoju psychozy przez negatywne schematy postrzegania siebie i innych oraz podejrzliwość (Kilcommons i Morrison, 2005).…”
Section: Stan Ryzyka Rozwoju Psychozyunclassified